Creating business opportunity by restoration of Gombak River and humanising entrepreneurship programme in Kg Sungai Chinchin - Md Saipuanuar, Muhamad Taufiq; Ahmad Dahlan, Abdul Rahman (Research Publish Journals, 2019)
River is important as it is a part of water resources on earth. It is a rich sources of fish and other aquatic life. Fresh water bring lot of benefits in human daily life such as drinking, cooking and washing clothes as well as for agriculture. The Sustainable Development Goals by the United Nation in life of land is focus on restoring the polluted river and improving the water quality. Irresponsible people that throw the rubbish in the river give a bad impact on it as it cause a river pollution and lot of rubbish floating in the river. Hence, the purpose of this paper is to propose a conceptual business model for the Gombak River restoration and sustainability inland fresh water ecosystems including humanising education through eLearning, mentoring programme and eMarketplace to help local community in Kg Sungai Chinchin. Through this business model, the river can be restored and human can utilise the ecosystem with various benefits in a sustainable way. It can also create business and job opportunity along the riverside, and reduce the enemployment among the local community in Kg. Sungai chinchin. The finding shows that the restoration project has a potential to improve health quality and community safety. Meanwhile, it has the potential in strengthening the economy and increase employment through the humanising entrepreneurship education. This paper adapted the design thinking approach where literature review and interviews were conducted to understand the issue, analyse, formulate and validate the conceptual business model and solution. Business modelling tools like the Business Model Canvas (BMC) and Value Proposition Canvas (VPC) are used in formulating an initial business model for the programme. The initial business model is then validated by customer segment. BMC is a business tool used to visualise all the building blocks of starting a business or programme, including customers, route to market, value proposition and revenue stream. While, VPC is to ensure that a product or service is positioned around customer values and needs.